Design and evaluation of a continuum robot with extendable balloons - E. Y. Yarbasi; E. Samur (Mechanical Sciences, 2018)
This article presents the design and preliminary evaluation of a novel continuum robot actuated by two extendable balloons. Extendable balloons are utilized as the actuation mechanism of the robot, and they are attached to the tip from their slack sections. These balloons can extend very much in length without having a significant change in diameter. Employing two balloons in an axially extendable, radially rigid flexible shaft, radial strain becomes constricted, allowing high elongation. As inflated, the balloons apply a force on the wall of the tip, pushing it forward. This force enables the robot to move forward. The air is supplied to the balloons by an air compressor and its flow rate to each balloon can be independently controlled. Changing the air volumes differently in each balloon, when they are radially constricted, orients the robot, allowing navigation. Elongation and force generation capabilities and pressure data are measured for different balloons during inflation and deflation. Afterward, the robot is subjected to open field and maze-like environment navigation tests. The contribution of this study is the introduction of a novel actuation mechanism for soft robots to have extreme elongation (2000 %) in order to be navigated in substantially long and narrow environments.